Biocompatible hydroxylated boron nitride nanosheets/poly(vinyl alcohol) interpenetrating hydrogels with enhanced mechanical and thermal responses - Jing, Lin (2018)
Poly(vinyl alcohol) (PVA) hydrogels with tissue-like viscoelasticity, excellent biocompatibility, and high hydrophilicity have been considered as promising cartilage replacement materials. However, lack of sufficient mechanical properties is a critical barrier to their use as load-bearing cartilage substitutes. Herein, we report hydroxylated boron nitride nanosheets (OH-BNNS)/PVA interpenetrating hydrogels by cyclically freezing/thawing the aqueous mixture of PVA and highly hydrophilic OH-BNNS (up to 0.6 mg/mL, two times the highest reported so far). Encouragingly, the resulting OH-BNNS/PVA hydrogels exhibit controllable reinforcements in both mechanical and thermal responses by simply varying the OH-BNNS contents. Impressive 45, 43, and 63% increases in compressive, tensile strengths and Young’s modulus, respectively, can be obtained even with only 0.12 wt% (OH-BNNS:PVA) OH-BNNS addition. Meanwhile, exciting improvements in the thermal diffusivity (15%) and conductivity (5%) can also be successfully achieved. These enhancements are attributed to the synergistic effect of intrinsic superior properties of the as-prepared OH-BNNS and strong hydrogen bonding interactions between the OH-BNNS and PVA chains. In addition, excellent cytocompatibility of the composite hydrogels was verified by cell proliferation and live/dead viability assays. These biocompatible OH-BNNS/PVA hydrogels are promising in addressing the mechanical failure and locally overheating issues as cartilage substitutes and may also have broad utility for biomedical applications, such as drug delivery, tissue engineering, biosensors, and actuators.